Creating content with Markdown - Terpstra, Brett; Safari eBooks ([San Francisco, CA?] : Peachpit, 2014)
"Markdown is the easiest way to create web (HTML) content, and can be used to generate PDFs, Word and other documents with all the flexibility of CSS styling. The syntax is easy to learn and the various flavors of Markdown extend it to a point where it's adaptible enough to handle most needs. Working in plain text means creating future-proof documents that can shift with the changing tides of content creation tools and presentation formats. It's an ideal means of content creation for everyone from web professionals to office workers, and from casual bloggers to authors of long-form works. This course begins by explaining the basic syntax of Markdown, as defined by John Gruber and goes on to explore other versions of Markdown, including MultiMarkdown, GitHub Flavored Markdown, Kramdown and others. It finishes by showing how to turn your Markdown into web content and polished documents."--Resource description page.
Title from resource description page (viewed Apr. 24, 2014).
Presenter, Brett Terpstra.
Keywords: HTML (Document markup language); File conversion (Computer science); Text editors (Computer programs); Portable document software; Electronic books